The Local Tradition of Magical Practices in Banten Society - Humaeni, Ayatullah (el Harakah: Jurnal Budaya Islam, 2012)
This article aims to discuss the cultural phenomenon of magical practices in the Muslim society of Banten which still exists up to the present. It is a part of my MA thesis research that has been combined with my recent field research using ethnography method based on the anthropological approach. Magical practices becomes cultural identity for Bantenese society.  Several sources on Banten mention that Banten as a central spot for magical sciences, besides it is also well- known as a religious area. The magical practices are still regarded important for Bantenese people, especially who live in the villages to solve their practical problems in their social life. Magic is a socio-religious phenomenon which has long, well-established roots in Banten society. It  is  traceable from many literatures that describes the uniqueness of Bantenese’s culture. Besides other magical practices debus is the most noticeable appearance of the magical tradition in Banten since the sultanate period until nowadays. The existence of debus Banten and other kinds of magical practices in Banten has strengthened the reputation of Banten as if ‘a haven of magical sciences’. Tulisan ini mencoba mendiskusikan tentang fenomena kultural mengenai praktek magis pada masyarakat Muslim Banten yang masih ada hingga saat ini. Artikel ini merupakan bagian dari tesis Master saya yang sudah dikombinasikan dengan penelitian lapangan baru-baru ini dengan menggunakan metode etnografi berdasarkan pendekatan antropologis. Praktek magis sudah menjadi identitas kultural bagi masyarakat Banten. Beberapa sumber menyebut Banten sebagai pusat ilmu-ilmu gaib, di samping dikenal sebagai daerah yang religius. Praktek magis masih dianggap penting bagi masyarakat Banten, khususnya yang tinggal di pedesaan untuk menyelesaikan masalah-masalah praktis dalam kehidupan sosial mereka. Magis adalah sebuah fenomena sosio-kultural yang memiliki akar yang cukup lama dan sudah berakar kuat dalam masyarakat Banten. Hal ini bisa dilacak dari banyak literatur yang menjelaskan keunikan dari budaya Banten. Debus adalah bukti paling kongkrit dari tradisi magis di Banten sejak periode kesultanan hingga saat ini, disamping beragam praktek magis yang lainnya. keberadaan debus Banten dan berbagai jenis praktek magis yang lainnya di Banten telah memperkuat reputasi Banten sebagai ‘tempat bersemayamnya ilmu-ilmu magis’.